2008
DOI: 10.1111/j.1747-0285.2008.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nanoparticles as Novel Immunogens: Design and Analysis of a Prototypic Severe Acute Respiratory Syndrome Vaccine

Abstract: Severe acute respiratory syndrome (SARS) is an infectious disease caused by a novel coronavirus that cost nearly 800 lives. While there have been no recent outbreaks of the disease, the threat remains as SARS coronavirus (SARS-CoV) like strains still exist in animal reservoirs. Therefore, the development of a vaccine against SARS is in grave need. Here, we have designed and produced a prototypic SARS vaccine: a self-assembling polypeptide nanoparticle that repetitively displays a SARS B-cell epitope from the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
173
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(180 citation statements)
references
References 35 publications
6
173
1
Order By: Relevance
“…As shown in Figure 1, we were able to obtain particles in both cases with sizes between 16-25 nm. The size and morphology of the nanoparticles closely resembled those obtained in bacteria (Babapoor et al, 2011;Kaba et al, 2009;Pimentel et al, 2009). This data demonstrated that nanoparticles were successfully Uribe-Campero et al 1603 formed in the plant cytoplasm.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…As shown in Figure 1, we were able to obtain particles in both cases with sizes between 16-25 nm. The size and morphology of the nanoparticles closely resembled those obtained in bacteria (Babapoor et al, 2011;Kaba et al, 2009;Pimentel et al, 2009). This data demonstrated that nanoparticles were successfully Uribe-Campero et al 1603 formed in the plant cytoplasm.…”
Section: Resultssupporting
confidence: 63%
“…When the sequence of these nanoparticles was expressed in E. coli and purified, no particles were obtained, they had to be subjected to several folding treatments in vitro for the particles to assemble (Raman et al, 2006;Pimentel et al 2009). However, in our case, the nanoparticles were able to self-assemble spontaneously in the plant cytoplasm without any further treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have extensively used exogenous lipids and polymers to form self-adjuvanting delivery systems that obviate the use of toxic adjuvants [8][9][10][11][12][13]. Recently, it has been reported that self-assembled peptides exclusively composed of endogenous amino acids were able to stimulate immune responses [14][15][16].…”
Section: Introductionmentioning
confidence: 99%